ANALISIS INDISPLINER KERJA KARYAWAN PADA PG KREBET BARU - Yunita Listy Aryawati; Roziana Ainul Hidayati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
The purpose of this study was to find out and analyze the discipline of PG Krebet Baru employees. The method used by the authors in this study is the use of descriptive qualitative methods. The data collection technique used is through interviews and secondary data sources. In taking the sample, the researcher took 4 informants to be interviewed. Judging from the observations of researchers that there are still many employees who take disciplinary actions, the factors causing employees to still take many disciplinary actions are due to being late in providing confirmation of explanations to superiors or the attendance team. And the lack of strict sanctions that lead to disciplinary actions is still increasing.